-8m-6=12-5m

Simple and best practice solution for -8m-6=12-5m equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8m-6=12-5m equation:


Simplifying
-8m + -6 = 12 + -5m

Reorder the terms:
-6 + -8m = 12 + -5m

Solving
-6 + -8m = 12 + -5m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '5m' to each side of the equation.
-6 + -8m + 5m = 12 + -5m + 5m

Combine like terms: -8m + 5m = -3m
-6 + -3m = 12 + -5m + 5m

Combine like terms: -5m + 5m = 0
-6 + -3m = 12 + 0
-6 + -3m = 12

Add '6' to each side of the equation.
-6 + 6 + -3m = 12 + 6

Combine like terms: -6 + 6 = 0
0 + -3m = 12 + 6
-3m = 12 + 6

Combine like terms: 12 + 6 = 18
-3m = 18

Divide each side by '-3'.
m = -6

Simplifying
m = -6

See similar equations:

| 7(y-3)+2(y+4)=14 | | P(-2)=-4x^3-x^2+2x | | -3m+14=4m+7 | | 11n-12n= | | -10+4x=9+12x | | 11+2p=17 | | (9x+20)+(7x+2y)=180 | | 7+3f=19 | | 5x+3-6x=8 | | m^2+10m=c | | 3(3z-1)-3(3-2z)=9 | | h=-0.05x^2+x+3 | | 13p+17q+p-6q-3p= | | y=-8x(x-2) | | 3p-13=11 | | M-35=21whatism | | -5x/3=5/2 | | 6x=22.5 | | x-3/7x | | -2=4x-6 | | 4+2p=12 | | 6(z-3)=3(z+1)+3 | | 72/8=48/12 | | 5x-15=27-2x | | -8x-18=30+-2x | | -2x+26=2x+10 | | 5x+4=-3x+13 | | 3n+12=24 | | 6+2(Z-3)=-5z+3 | | 11m+5n-5m+7n= | | 56=10log(x) | | 2m=16-9 |

Equations solver categories